Hypertension amongst pregnant women in rural low-resource settings: is antenatal detection of pre-eclampsia adequate?. (18th April 2012) - Hezelgrave, NL; Hamid, F; Solangon, A; Bateman, A; Perry, R; Abid, S; Dempsey, A; Saad, L; Ashraf, D; Pearce, A; Blennerhassett, A; Page, M; et al.
Abstract : Introduction: 10–15% of maternal mortality global maternal mortality is thought to be attributable to pre-eclampsia, claiming up to 40, 000 women's lives each year. In many developing world settings countries, pre-eclampsia is frequently under-detected not only because antenatal attendance is low, but also inadequate training in accurate blood pressure(BP) measurements and poor equipment quality.1 2 3 Objective: To determine the prevalence of hypertension in pregnancy and the unmet need for antenatal blood pressure measurement amongst women presenting to hospital in rural and semi-rural sub-Saharan Africa and Pakistan-administered Kashmir. Method: Prospective observational study: Antenatal (>20 weeks) and postpartum (<7 days) populations who accessed care at a central referral site served by rural clinics in 5 countries; Ethiopia, Zambia, Zimbabwe, Tanzania, Kashmir. Systematic blood pressures were taken using an automated, validated BP device. Results: Data from 926 women (454 inpatients, 472 outpatients, mean antenatal gestational age 32.7 weeks) were analysed. 93/926 (10.0%) had sustained hypertension (>140/90). 282/926 (30.5%) had never had a BP taken in their index pregnancy. Discussion: >30% of pregnant or immediately post-partum women had no previous antenatal BP measurement during their pregnancy, either due to insufficient provision of this service or poor uptake. That these were women who had accessed referral level care implies significant levels of undetected pre-eclampsia in the community. Urgent research is needed to establish the optimal way to deliver BP monitoring: Could antenatal BP measurement be improved with the availability of a validated, simple to use BP machine for use by a community health workers or rural clinics?